The strategic dilemma of counter-cyclical capital investment. (18th June 2021) - Larson, Eric C.; Vieregger, Carl
This research investigates the timing of strategic investment decisions in response to changing conditions in the macro-economic environment. Managers face a strategic dilemma when making capital investments within the macro-economic cycle: even though resources may be scarce during downturns, firms with managerial capabilities can exploit factor markets to make profitable investments. We first show that managers recognise the importance of investing through economic downturns (i.e., investing counter-cyclically), but we also hypothesise and show that firms invest less during economic contractions (i.e., they do not invest counter-cyclically). We then hypothesise and find that performance is declining in investment, suggesting that contingent factors may influence successful capital investments. Our main hypothesis and test demonstrate that firms increasing capital investment during macro-economic downturns experience greater forward performance over one, two, and three-year horizons. We also show that the underlying mechanisms of this increased performance may be the temporal orientation (i.e., investment horizon) of strategic capital allocation and the firm's dependence on external sources of financing. The analyses in this paper suggest that executives should make capital investments when it is perhaps the most difficult to do so.